Crystal Structure and Thermal Chemical Properties of Tetraaquabis(N´ -acetoxylbenzimidazole- N-acetoxyl-κO)-Cobalt(II) dihydrate - Zhang, Shu-Sheng; Ding, Cai-Feng; Tian, Bing-Qing; Li, Xue-Mei; Hu, Hong; Ouyang, Ping-Kai (Asian Journal of Chemistry, 2010)
The crystal structure of tetraaquabis(N´-acetoxyl-benzimidazole-Nacetoxyl-κO)-cobalt(II) dihydrate has been determined by single crystal X-ray diffraction method. the molecules are linked by NI-HIA………O3 intermolecular interactions into zig-zag chains. The packing is stabilized by dipole-dipole and van der Waals forces.